Proteome and Nutritional Shifts Observed in Hordein Double-Mutant Barley Lines - Bose, Utpal; Juhász, Angéla; Yu, Ronald; Bahmani, Mahya; Byrne, Keren; Blundell, Malcolm; Broadbent, James A.; Howitt, Crispin A.; Colgrave, Michelle L. (Frontiers in Plant Science, 2021)
Lysine is the most limiting essential amino acid in cereals, and efforts have been made over the decades to improve the nutritional quality of these grains by limiting storage protein accumulation and increasing lysine content, while maintaining desired agronomic traits. The single lys3 mutation in barley has been shown to significantly increase lysine content but also reduces grain size. Herein, the regulatory effect of the lys3 mutation that controls storage protein accumulation as well as a plethora of critically important processes in cereal seeds was investigated in double mutant barley lines. This was enabled through the generation of three hordein double-mutants by inter-crossing three single hordein- mutants, all at backcross 3 times with the malting barley cultivar Sloop. Proteome abundance measurements were integrated with their phenotype measurements, proteins were mapped to chromosomal locations and to their corresponding functional classes. These models enabled the prediction of previously unknown points of crosstalk that connect the impact of lys3 mutations to other signalling pathways. In combination, these results provide an improved understanding of how the mutation at the lys3 locus remodels cellular functions and impact phenotype that can be used in selective breeding to generate favourable agronomic traits.